Effect of surfactants and inducers on increased uricase production under submerged fermentations by Bacillus cereus - Khade S.; Srivastava S.K. (My University, 2025)
Uricase is a clinical enzyme used for the oxidation of uric acid crystals in gout disease. The present study aimed to increase the suitable surfactant-mediated uricase production on induction by different concentrations of inducers. The efficiency of Bacillus cereus to produce extracellular uricase enzyme was studied in uric acid-containing agar plates. Among the studied inducers, uric acid is the potential inducer for uricase production under submerged fermentations (SMF), which induced 19.41 U/ml uricase in medium containing 2.0 g/L of uric acid, however further increase in the uric acid concentration decreased uricase production, which could be because of substrate inhibition. The physical parameters including agitation speed (rpm) and time duration (h) of uricase production were optimized and found to produce optimum uricase at 150 rpm in 26 h of SMF. Among the studied surfactants, nonionic surfactant, polyvinyl alcohol has shown a remarkable increase in the uricase production of 31.58 U/ml, which is a 61% increase under optimized conditions in SMF. The stability of produced uricase was found at pH 7.5 and temperature 30°C. Also the effects of various metal ions (1 mM) on the uricase activity were studied and observed to be inhibitory in nature in the descending order K+ > Ca2+ > Zn2+ > Fe3+ > Ni2+ > Mg2+ > Mn2+ > Cu2+. © 2017, Copyright © Taylor & Francis Group, LLC.